Risk of osteoarthritis in patients with hidradenitis suppurativa: a global federated health network analysis - Chang, Hui-Chin; Wu, Chih-Lung; Chiu, Tsu-Man; Liao, Wen-Chieh; Gau, Shuo-Yan (Frontiers in Immunology, 2023)
Abstract Background Osteoarthritis and Hidradenitis suppurativa (HS) share common inflammatory pathway. However, whether HS patients have higher risk developing osteoarthritis remained unclear. Methods A retrospective cohort design was adopted in this study. Electronic medical records had been retrieved from the US collaborative network in the TriNetX research network. 1:1 propensity score matching was performed to match for covariates. In total, 50,931 patients with HS and the same amount of non-HS controls were identified for analyses. Hazard ratio of osteoarthritis in HS patient were calculated. Results Risk of patients with HS developing osteoarthritis was 1.37-fold higher than non-HS controls (95% CI, 1.21,1.55) when followed-up for one year. The significance remained when the follow-up periods were extended to three years and five years. When osteoarthritis was stratified on occurring sites, the HR of knee osteoarthritis was 1.19 (95% CI, 1.09-1.29) and the HR of hip osteoarthritis was 1.17 (95% CI, 1.01-1.35) in five-year follow-up. The five-year risk of osteoarthritis remained significant in sensitivity models. Conclusion HS patients were of high risk of developing osteoarthritis while comparing with people without HS. The clinical association were recommended to be considered while approaching HS patients.